Effects of Y chromosome Microdeletions on Male Fertility - Sajadi, Hesamoddin; Taghizabet, Neda; Aliakbari, Fereshteh; Rezaei-Tazangi, Fatemeh; Sedighi Gilani, Mohammad Ali (Archives of Men's Health, 2021)
Background: In the process of human reproduction, spermatogenesis is one of the most important stages, which is controled by special genes on Y chromosome. Previous studies show that some infertile men have microdeletions on Y chromosome, which cause the reduction of sperm count. Three prominent spermatogenesis loci have been identified on the Y chromosome and entitled “azoospermia factors” (AZFa, b, and c). Hereby, this review article aimed to investigate the content of the Y chromosome microdeletions and their importance in male fertility. Methods: Data and information were collected on English-language articles from PubMed and MEDLINE databases. For Persian articles, Persian-language databases, including SID Scientific Database, IranMedex Medical Articles Database, IranDoc (Iran Scientific Information and Documents Research Institute), Magiran Publication Information, and MedLib were investigated. More than 50 articles on Y chromosome microdeletions and infertility published during 2000-2020 were studied. Results: Previous studies implicated that Y chromosome microdeletions in AZFa, AZFb, and AZFc regions are accompanied by defect in spermatogenesis, leading to oligo / azoospermia. Patients with AZFa and AZFb microdeletions present secretory azoospermia and do not have sperm in their seminiferous tubules. Complete AZFc deletion involves region b2/b4, which contains a total of 12 genes. Incomplete deletion of AZFc includes b1/b3, b2/b3 and gr/gr. The most common of which are gr/gr. In men with gr/gr deletion, sperm count and motility were lower than control group. Conclusion: Y chromosomal microdeletions emerged as the most frequent structural chromosome anomaly associated with the quantitative reduction of sperm. The development of assisted reproductive techniques (ART) like intra-cytoplasmic sperm injection (ICSI) and testicular sperm extraction (TESE) helps to bypass the natural barriers of fertilization.